Intellectual property in the Trans-Pacific Partnership: Increasing the barriers for the access to affordable medicines - Carlos María Correa (South Centre, 2017)
Most free trade agreements (FTAs) signed by the United States, the European Union and the members of the European Free Trade Association (EFTA) in the last 15 years contain chapters on intellectual property rights with provisions applicable to pharmaceuticals. Such provisions considerably expand the rights recognized to pharmaceutical companies under the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) established in the context of the World Trade Organization (WTO). The text on intellectual property of the Trans-Pacific Partnership (TPP) goes further than those FTAs. It reflects the ambition of such companies to obtain even higher levels of protection. This paper discusses some characteristics of the TPP negotiations and their main outcomes, and how the adopted TRIPS-plus provisions may negatively affect access to medicines, notably in developing countries that may become parties to that agreement.
Keywords: 300; Immaterialgüterrechte; Arzneimittel; TRIPS; Freihandelsabkommen; USA; EU-Staaten